2017
DOI: 10.1186/s13036-017-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of stromal cell-derived factor 1α for in situ tissue regeneration

Abstract: In situ tissue regeneration approach aims to exploit the body’s own biological resources and reparative capability and recruit host cells by utilizing cell-instructive biomaterials. In order to immobilize and release bioactive factors in biomaterials, it is important to engineer the load effectiveness, release kinetics and cell recruiting capabilities of bioactive molecules by using suitable bonding strategies. Stromal cell-derived factor 1α (SDF-1α) is one of the most potent chemokines for stem cell recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 125 publications
2
52
0
1
Order By: Relevance
“…Due to the complexity of native bone healing, a wide range of efforts have explored the use of these and other factors to accelerate cell recruitment and regenerative activity. For example, stromal derived factor 1 and platelet derived growth factor have been delivered from bonemimetic scaffolds to increase cell migration in vitro 34 and improve bone healing in vivo 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of native bone healing, a wide range of efforts have explored the use of these and other factors to accelerate cell recruitment and regenerative activity. For example, stromal derived factor 1 and platelet derived growth factor have been delivered from bonemimetic scaffolds to increase cell migration in vitro 34 and improve bone healing in vivo 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence in the field of regenerative medicine suggests that cell recruitment stimulates latent self‐repair mechanisms in patients and harnesses the innate capacity for tissue regeneration (Chen, Wu, Zhang, Zhang, & Sun, ). This strategy has been explored as an alternative to cell‐based therapies for in situ tissue regeneration of heart, cartilage and bone tissue (French, Somasuntharam, & Davis, ; Ji et al., ; Zhao, Jin, Li, Qiu, & Li, ). Instead of introducing ex vivo expanded stem cells, recruiting endogenous cells relies on active attraction of regenerative cells to a site of tissue damage or injury.…”
Section: Introductionmentioning
confidence: 99%
“…As the mechanism underlying this enhanced periodontal regeneration, Zhou et al have found that bone marrow-derived stem cells migrated preferentially to the periodontium over other organs to get involved in periodontal regeneration (Zhou et al, 2011). In addition to this cell recruitment efficacy, SDF-1α is anticipated to modify the inflammatory response and early wound healing (Chen et al, 2015;Dickinson et al, 2013;Zhao et al, 2017).…”
mentioning
confidence: 99%
“…Additionally, this approach overcomes the poor integration of in vitro new tissue that commonly occurs after implantation (Smits et al, 2016). Based on this, in situ tissue regeneration intends to promote regeneration, taking advantage of the native microenvironment of the injury site through the implantation of tissue-specific biomaterials combined or not with biomolecules or cells (Figure 1) Zhao et al, 2017). This approach is a dynamic process in which cells recruited from host or delivered by the scaffold must proliferate, self-assemble, and differentiate before reaching a steady-state (Murdock and Stephen, 2017).…”
Section: Materials For In Situ Tissue Regenerationmentioning
confidence: 99%